Racionalidade e projeto político-pedagógico: um olhar a partir do currículo e do relato das práticas docentes de professores do curso de Ciências Contábeis da Universidade Federal do Ceará - Pinho, Ruth Carvalho de Santana (2010)
The effective model in the university academic units shows that something needs to be changed in higher education. However, since it is not perceived that the problem is in the proper rationality itself, the way of surpass has been to reiterate old practices, increasing class time and disciplines and also moving some units requirements. Understanding the pedagogical rationality as established element of the educative action, it became relevant to investigate how it integrates the political pedagogical project, the curriculum and the faculty members practices in the Undergraduate Accounting Program of the Federal University of Ceará-UFC. The understanding of the multiple realities lived within University and the reflection concerning the process of the related Course management and the faculty job, will be able consequently to contribute for the improvement of the process teach-learning and also the professional formation of the egresses. Thus, the main purpose of this work is to analyze the aspects of the faculty pedagogical rationality of the Undergraduate Accounting Program of UFC that propitiate to the Political-Pedagogical Project through the Curriculum and the Faculty Practices and establish the educative action based on principles of a reflexive and changing understanding. Based on the nature of the elements to be analyzed and also on the function of the research problem it was opted to the modality of collaborative research, using research techniques such as focal group interviews and reflexive sessions. A documental research with a descriptive analysis of the Political Pedagogical Project was also done before, followed by the application of questionnaires in order to raise the faculty profile. It was concluded that a reflexive and transforming educative action will be propitiated by the Political Pedagogical Project through the Curriculum and the Faculty practices since the identified pedagogical rationality even based on technique nature, reach an epistemological platform establishing a faculty job supported by knowledge resultant of the pedagogical praxis.